Reconstructing the Worlds of Wildlife: Uexküll, Hediger, and Beyond - Chrulew, Matthew (SPRINGER, 2020)
The theoretical biology of Jakob von Uexküll has had significant conceptual and practical afterlives, in Continental philosophy, biosemiotics and elsewhere. This paper will examine the utilisation of Uexküll in twentieth-century zoo biology and its significance for relating to wildlife in hybrid environments. There is an important though rarely analysed line of inheritance from von Uexküll to Heini Hediger, the Swiss zoo director and animal psychologist. Hediger’s fundamental theoretical position began from the construction of the world from the animal’s point of view, as determined by factors including species specific phylogeny, individual and group biography, and anthropogenic circumstance. He operationalised Uexküll’s approach to animal worlds in order to optimise the design of zoo enclosures, considered as both physical and psychological habitats, in which captive wildlife could flourish. This subjectivist and phenomenological perspective has often been sidelined in zoo biology by more objectivist and mechanising approaches. Nonetheless, Hediger’s work and thought, through its inheritance from Uexküll, has important implications for twenty-first century relations with wildlife.